Effects of pregnant mothers’ work on first-year infant deaths in a Thai prospective cohort - Tiwarat Tor. jarern (2017)
This study examines the relationship between mothers' work and infant death in Thailand. It estimates the survival probability at a given time using data from a prospective cohort study of Thai children during 2000-2002. A cohort of 4,245 infants was followed from 28-32 weeks gestation until one year of age. The study found that mother’s occupation had an independent relationship with infant death (p< 0.10). Infants of mothers with mid-level occupations during pregnancy showed a lower risk of death than those with lower level occupations (odds ratio = 0.42, p= 0.082). In addition, the Kaplan-Meier cumulative probabilities of survival support the finding that this difference occurred in the late-neonatal and post-neonatal periods. However other factors occurring during pregnancy and the neonatal period—namely a lack of attended antenatal care, low birthweight, preterm birth, perinatal hospitalization morbidity of the mother, income of the household head, and geographic area— also increased the risk of infant death. The findings indicate that the Thai government should be concerned about working conditions for female agricultural workers and construction laborers, and that pregnant women and their families should be encouraged to access both pre- and post-natal maternal and child health services, especially in the late and post-neonatal periods. Such measures would save infant lives and lower the infant mortality rate for Thailand.